Exercise intolerance in comorbid COPD and heart failure: the role of impaired aerobic function. Issue 4 (18th April 2019) - Rocha, Alcides; Arbex, Flavio F.; Sperandio, Priscila A.; Mancuso, Frederico; Marillier, Mathieu; Bernard, Anne-Catherine; Alencar, Maria Clara N.; O'Donnell, Denis E.; Neder, J. Alberto
Impaired aerobic function is a potential mechanism of exercise intolerance in patients with combined cardiorespiratory disease. We investigated the pathophysiological and sensory consequences of a low change in oxygen uptake (Δ V ′O2 )/change in work rate (ΔWR) relationship during incremental exercise in patients with coexisting chronic obstructive pulmonary disease (COPD) and systolic heart failure (HF). After clinical stabilisation, 51 COPD–HF patients performed an incremental cardiopulmonary exercise test to symptom limitation. Cardiac output was non-invasively measured (impedance cardiography) in a subset of patients (n=18). 27 patients presented with Δ V ′O2 /ΔWR below the lower limit of normal. Despite similar forced expiratory volume in 1 s and ejection fraction, the low Δ V ′O2 /ΔWR group showed higher end-diastolic volume, lower inspiratory capacity and lower transfer factor compared to their counterparts (p<0.05). Peak WR and peak V ′O2 were ∼15% and ∼30% lower, respectively, in the former group: those findings were associated with greater symptom burden in daily life and at a given exercise intensity (leg discomfort and dyspnoea). The low Δ V ′O2 /ΔWR group presented with other evidences of impaired aerobic function (sluggish V ′O2 kinetics, earlier anaerobic threshold) and cardiocirculatory performance (lower oxygen pulse, lower stroke volume and cardiac output) (p<0.05). Despite similar exertional hypoxaemia, they showed worse ventilatory inefficiency and higher operating lung volumes, which led to greater mechanical inspiratory constraints (p<0.05). Impaired aerobic function due to negative cardiopulmonary–muscular interactions is an important determinant of exercise intolerance in patients with COPD–HF. Treatment strategies to improve oxygen delivery to and/or utilisation by the peripheral muscles might prove particularly beneficial to these patients. Impaired aerobic function due to negative cardiopulmonary–muscular interactions is an important determinant of exercise intolerance in patients with comorbid COPD and heart failure http://ow.ly/gveW30nxsUG